The MAUT and SAW Methods in Recruiting Employees at PT. Bengkel Sehat - Vania, Dea Ersa; Akbar, Muhammad Barkah (SEAN Institute, 2023)
The phenomenon that occurs at PT. Bengkel Sehat, namely the company does not have a system for recruiting employees with accurate data, in the manual process it is preceded by an administrative selection of application files from prospective workers, this selection is selected by comparing application files between prospective workers according to the criteria. Frequent errors in inputting assessment data and calculating values ​​based on the dimensions set at PT. Healthy Workshop. PT. Healthy Workshop does not use the Multi-Attribute Utility Theory (MAUT) and Simple Additive Weighting (SAW) methods in making decisions in hiring employees. The system design uses the PHP programming language and MySQL database. The computer specifications used are at least dual core, 4GB RAM and 120 Gb Hard Drive. The method used in designing this application is blackbox testing. Black box testing is a test that is carried out only by observing the results of execution through test data and checking the functionality of the software. The results of this study are to minimize errors in inputting prospective employee assessment data, to reduce the risk of errors in assessing prospective employee data and implementing a decision support system using the Multi-Attribute Utility Theory (MAUT) and Simple Additive Weighting (SAW) methods. provide users with a more accurate decision value.